ACUTE AND CHRONIC TOXICITY STUDIES OF THE WATER EXTRACT FROM DRIED FRUITS OF TERMINALIA BELLERICA (GAERTN.) ROXB. IN SPARGUE-DAWLEY RATS - Sireeratawong, Seewaboon; Jaijoy, Kanjana; Panunto, Watcharin; Nanna, Urarat; Lertprasertsuke, Nirush; Soonthornchareonnon, Noppamas (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Acute and chronic toxicities of the water extract from the dried fruits of Terminalia bellerica (Gaertn.) Roxb. were assessed in both female and male rats. For the study of acute toxicity, a single oral administration of the water extract at a dose of 5,000 mg/kg body weight (10 female, 10 male) was performed and the results showed no signs of toxicity such as general behavior changes, morbidity, mortality, changes on gross appearance or histopathological changes of the internal organs of rats. The study of chronic toxicity was determined by oral feeding both female and male rats (10 female, 10 male) daily with the test substance at the dose of 300, 600 and 1,200 mg/kg body weight continuously for 270 days. The examinations of signs of toxicity showed no abnormalities in the test groups compared to the controls. In addition, these rats were analyzed for final body and organ weights, necropsy, as well as hematological, blood chemical and histopathological parameters. Taken together, the water extract from the dried fruits of T. bellerica did not cause acute or chronic toxicities in either female or male rats.